Web Services and Widgets for Library Information Systems - Back, Godmar; Bailey, Annette (Information Technology and Libraries, 2010)
As more libraries integrate information from web services to enhance their online public displays, techniques that facilitate this integration are needed. This paper presents a technique for such integration that is based on HTML widgets. We discuss three example systems (Google Book Classes, Tictoclookup, and MAJAX) that implement this technique. These systems can be easily adapted without requiring programming experience or expensive hosting.